Epidemiological and clinico-biochemical studies on iodine deficiency in dairy animals of Punjab - KAUR, KHUSHDEEP; RANDHAWA, S S (The Indian Journal of Animal Sciences, 2014)
The present investigation assesses the iodine status of dairy animals and evaluates the diagnostic significance of plasma thyroid hormones as well as total plasma cholesterol concentration in iodine deficiency. In iodine deficient dairy animals, comprehensive anamnesis revealed the observance of repeat breeding and anestrous, as the predominant manifestations. Significantly low plasma inorganic iodine (PII-45.66:±A.02µg/L) and urinary iodine (UI-57.27±5. 78µg/L) levels were recorded in deficient animals as compared to those of healthy animals. Prevalence rate of sub-clinical iodine deficiency in cows and buffaloes was 72.22 and 76.66% respectively. Mean concentrations of plasma cholesterol increased Significantly and T4 concentrations decreased significantly in deficient cows (121.59±3.32mg/dl and 38,45±1.96nmol/L) as compared to healthy ones (II 7.52±2.66mgldl and 44.62±0.664nmol/L) respectively. The mean T3 (1.84±0.132nmol/L) and T4 (35.08± 1.37nmol/L) levels showed significant fall in deficient buffaloes. The results revealed that PH and UI levels were sensitive indicators for detecting iodine deficiency in dairy animals. The study also revealed the unreliability of total plasma cholesterol and thyroid hormones as screening diagnostic tests in iodine deficiency.